PENGAMPUNAN TINDAK PIDANA KORUPSI: SOLUSI ATAU KEMUNDURAN HUKUM DI INDONESIA - Hasibuan, Lawali (Universitas Harapan Medan, 2024)
The government's discourse in terms of granting pardons for corrupt crimes has generated a lot of controversy among the public and legal experts in Indonesia whether this democracy has experienced a legal setback because this pardon is not clearly and in detail regulated in Law Number 21 of 2001 concerning Eradication of Corruption Crimes because corruption has a different pattern from other criminal offences because criminal offences must be adjusted to the character of the crime. The research method used is normative juridical law or legal research library (search library), by analysing literature or secondary data that is relevant to the topic. This research is descriptive analytical, the data obtained and processed and analysed to provide a comprehensive picture of the forgiveness of corruption crimes regulated in Law Number 21 of 2011 concerning Corruption Crimes with data collection methods through document studies. The results of the study indicate that the pardon of corruption crimes regulated in the TIPIKOR Law is not effective and does not provide legal certainty to be implemented by law enforcement officials because there is no detailed law that regulates guardianship by paying or compensation for corruption crimes that harm state finances. Even if this is implemented by the government, it will experience a setback in democracy in the field of law enforcement and many people will carry out corruption with the assumption that criminal acts can be replaced by fines or refunds for corruption crimes committed.